2011
DOI: 10.1037/a0023584
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment for panic disorder with agoraphobia: A randomized controlled trial to examine the role of therapist-guided exposure in situ in CBT.

Abstract: Therapist-guided exposure is more effective for agoraphobic avoidance, overall functioning, and panic attacks in the follow-up period than is CBT without therapist-guided exposure. Therapist-guided exposure promotes additional therapeutic improvement--possibly mediated by increased physical engagement in feared situations--beyond the effects of a CBT treatment in which exposure is simply instructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 59 publications
10
183
0
5
Order By: Relevance
“…In contrast, patients who participated in the present study were treated with a specific therapeutic manual for panic disorder with agoraphobia [36]. This treatment manual has been found to be highly effective [7], also showing a high effect in this study (d=2.17) and a reduction of the symptoms comparable to previous studies [7].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 48%
See 2 more Smart Citations
“…In contrast, patients who participated in the present study were treated with a specific therapeutic manual for panic disorder with agoraphobia [36]. This treatment manual has been found to be highly effective [7], also showing a high effect in this study (d=2.17) and a reduction of the symptoms comparable to previous studies [7].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 48%
“…The therapy therefore lasted a total period of six weeks. A study by Gloster et al [7] showed the treatment manual to be highly effective. After each session, interim measurements were taken to record changes in symptom intensity.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of RCT studies and meta-analyses have shown overall evidence for the effectiveness of CBT for panic disorder/agoraphobia (Ruhmland & Margraf 2001;Mitte 2005;Haby et al 2006;Gloster et al 2011). Concerning the sustainability of the effects of CBT, findings are contradictory: Some studies found long-term success for CBT over a period of 1 to 2 years (Hunt & Andrews 1998;Stuart et al 2000;Gloster et al 2013;Fava et al 2001).…”
Section: Effectiveness and Sustainability Of Cbt For Anxiety Disordermentioning
confidence: 99%
“…Additionally, exposurebased interventions (including virtual reality exposure, Meyerbröker, 2014) show strong effect sizes in reducing agoraphobic avoidance behavior (Meyerbroeker et al, 2013;Moscovitch, 2009). Interestingly, therapist guidance during exposures appears important (Gloster et al, 2011). This large Randomized Control Trial showed that guided exposure in vivo was more effective than exposure without therapist guidance in reducing the number of panic attacks, avoidance behavior, and improvement in global functioning.…”
Section: Psychoeducationmentioning
confidence: 99%